2022
DOI: 10.3389/fmars.2021.796518
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal Fisher Association Leaders’ Estimates of Poaching in Their Exclusive Access Management Areas

Abstract: In marine environments, poaching can become a key threat to marine ecosystem conservation. Poaching can occur in marine protected areas and/or in fishery management areas. Unfortunately, understanding the magnitude and characteristics of poaching under community based and co-management governance schemes in coastal and marine environments, has not received the attention it deserves. In Chile, a system of Territorial Users Rights for Fisheries (TURF) has been recognized as one of the largest experiences of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Secondly, artisanal fishing in Chile and in particular the TURF system is highly vulnerable to illegal fishing (Gelcich et al, 2017;Oyanedel et al, 2018). Recent studies have shown that benthic resources are particularly exposed to poaching and illegal extraction (Romero et al, 2022). Restocking projects may generate a greater abundance of resources, and therefore greater incentives for illegal extraction (Caŕcamo et al, 2021).…”
Section: Social Implications Of Seaweeds Restockingmentioning
confidence: 99%
“…Secondly, artisanal fishing in Chile and in particular the TURF system is highly vulnerable to illegal fishing (Gelcich et al, 2017;Oyanedel et al, 2018). Recent studies have shown that benthic resources are particularly exposed to poaching and illegal extraction (Romero et al, 2022). Restocking projects may generate a greater abundance of resources, and therefore greater incentives for illegal extraction (Caŕcamo et al, 2021).…”
Section: Social Implications Of Seaweeds Restockingmentioning
confidence: 99%
“…In marine environments, LEK has been widely used to support management and monitoring of biodiversity, ecological dynamics, and fisheries (e.g., Olsson and Folke 2001;Moller et al 2004;Hind 2015;Kroloff et al 2019). For instance, it has helped to understand the causes and effects of Bonefish Albula vulpes decline in south Florida, United States (Kroloff et al 2019); to assess population trends of data-poor finfish species over the period 1950-2007 in the Philippines (Lavides et al 2009); to evaluate changes in spatial recreational fishing patterns from 1950 to 2010 in Puget Sound, United States (Beaudreau and Whitney 2016); to estimate illegal fishing in territorial user rights for fisheries systems in Chile (Romero et al 2022); and to assess the decline of several fish species in southeastern Brazil (Bender et al 2014), as well as several other examples (e.g., Close and Hall 2006;Ruddle and Hickey 2008;Taylor et al 2011;Loerzel et al 2017;Zapelini et al 2017). The ability of LEK to provide relevant and Pacific Beakfish Oplegnathus insignis, and Broomtail Grouper Mycteroperca xenarcha.…”
Section: Introductionmentioning
confidence: 99%
“…2009); to evaluate changes in spatial recreational fishing patterns from 1950 to 2010 in Puget Sound, United States (Beaudreau and Whitney 2016); to estimate illegal fishing in territorial user rights for fisheries systems in Chile (Romero et al. 2022); and to assess the decline of several fish species in southeastern Brazil (Bender et al. 2014), as well as several other examples (e.g., Close and Hall 2006; Ruddle and Hickey 2008; Taylor et al.…”
Section: Introductionmentioning
confidence: 99%